2018
DOI: 10.1016/s0016-5085(18)31107-7
|View full text |Cite
|
Sign up to set email alerts
|

1092 - Food Antigen-Specific Sensitization of Nociceptive Nerves as an Underlying Mechanism of Visceral Pain in Ibs

Abstract: Background: Exposure of a food antigen during stress, abdominal infection or ingestion of bacterial superantigens triggers in mice an aberrant immune response against this antigen leading to mast cell activation and visceral hypersensitivity upon re-exposure. As we previously reported histamine 1 receptor (H1R)-induced sensitization of TRPV1 in patients with irritable bowel syndrome (IBS), we hypothesized that a similar mechanism would be involved. Moreover, given that ingestion of food is a major trigger of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an elegant study, Aguilera-Lizarraga and Florens demonstrated that the establishment of oral tolerance can be impaired due to stress or intestinal infection, two major triggers of FGID symptoms, without triggering a systemic allergic reaction. Their results showed that this impaired tolerance triggered a mast cell activation through local (but not systemic) IgE, leading to colonic hypersensitivity and hyperpermeability ( 196 , 197 ).…”
Section: Food-related Models Of Fgidmentioning
confidence: 99%
“…In an elegant study, Aguilera-Lizarraga and Florens demonstrated that the establishment of oral tolerance can be impaired due to stress or intestinal infection, two major triggers of FGID symptoms, without triggering a systemic allergic reaction. Their results showed that this impaired tolerance triggered a mast cell activation through local (but not systemic) IgE, leading to colonic hypersensitivity and hyperpermeability ( 196 , 197 ).…”
Section: Food-related Models Of Fgidmentioning
confidence: 99%